2012
DOI: 10.1097/mcg.0b013e31825828a7
|View full text |Cite
|
Sign up to set email alerts
|

“Pre-cebo”

Abstract: Benefits of drugs in D-IBS drug trials have the potential to be influenced by preconceived notions derived from familiarity of drug class and the consent process even before the study begins which we refer to as the "pre-cebo" effect. The higher pre-cebo effect for rifaximin may be an obstacle to successful treatment effect during drug trials compared with drugs such as desipramine. The pre-cebo effect may need to be taken into account when formulating consent forms for IBS study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In classical drug RCT, unblinding will have imminent consequences for efficacy. Deliberate unblinding of RTC is usually only carried out when severe safety concerns arise but may also occur incidentally when patients and/or doctors notice significant differences in reporting of adverse events (64); even meta-analyses can identify such involuntary unblinding (65). Such unblinding will enhance the response to active therapy and reduce the response to control, thus enlarging the treatment–control difference (66).…”
Section: Common Control Problems In All Psychotherapy Trials and Theimentioning
confidence: 99%
“…In classical drug RCT, unblinding will have imminent consequences for efficacy. Deliberate unblinding of RTC is usually only carried out when severe safety concerns arise but may also occur incidentally when patients and/or doctors notice significant differences in reporting of adverse events (64); even meta-analyses can identify such involuntary unblinding (65). Such unblinding will enhance the response to active therapy and reduce the response to control, thus enlarging the treatment–control difference (66).…”
Section: Common Control Problems In All Psychotherapy Trials and Theimentioning
confidence: 99%
“…Previous studies have shown that such subjective assessments of IBS symptoms can be influenced by psychological factors. 38 Thus, our findings may have been similarly affected. Variation in dosage regimens between the different RCTs also represents a potential confounding factor.…”
Section: Discussionmentioning
confidence: 69%